MEMBANGUN â€œPENGANTINâ€ AL-QURâ€™AN DALAM PANDANGAN QURAISH SHIHAB - Naqiyah Naqiyah (Jurnal Penelitian Agama, 2020)
The basic concept of Shihabâ€™s Islamic family, if viewed from gender perspective is gender responsive on several aspects, but on other aspects looks gender biases. This phenomenon also revealed on Shihab's concept about manwomen relation inside family. On several aspect, Shihab trying to look equal by frequently using phrase â€œequalâ€ when discussion man-wife relation. Meanwhile, when confronting differences in reality, Shihab looks bias, because every difference always covered with different function, therefore he can't refuse role differences between man and wife.